2020
DOI: 10.1002/adfm.202007479
|View full text |Cite
|
Sign up to set email alerts
|

Charge Photogeneration in Non‐Fullerene Organic Solar Cells: Influence of Excess Energy and Electrostatic Interactions

Abstract: In organic solar cells, photogenerated singlet excitons form charge transfer (CT) complexes, which subsequently split into free charge carriers. Here, the contributions of excess energy and molecular quadrupole moments to the charge separation process are considered. The charge photogeneration in two separate bulk heterojunction systems consisting of the polymer donor PTB7‐Th and two non‐fullerene acceptors, ITIC and h‐ITIC, is investigated. CT state dissociation in these donor–acceptor systems is monitored by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 53 publications
2
34
0
Order By: Relevance
“…One can see that for B < 0.5 eV dissociation energies are too high and the CT state dissociation cannot be activated thermally. [47] We can therefore conclude that bias potentials on the order of 0.5 eV are required to dissociate CT state, in line with the results reported for one of the best performing NFA, Y6. [38]…”
Section: Dissociation Of the Charge Transfer Statesupporting
confidence: 87%
“…One can see that for B < 0.5 eV dissociation energies are too high and the CT state dissociation cannot be activated thermally. [47] We can therefore conclude that bias potentials on the order of 0.5 eV are required to dissociate CT state, in line with the results reported for one of the best performing NFA, Y6. [38]…”
Section: Dissociation Of the Charge Transfer Statesupporting
confidence: 87%
“…A phenomenological fit with 6), combined with the electrostatic interfacial bias, B(d) = B exp (−[(d + d 0 )/w] 3 ), is shown for w = 2 nm, d 0 = 1 nm and a range of bias potentials. One can see that for B < 0.5 eV dissociation energies are too high and the CT state dissociation cannot be activated thermally [47]. We can therefore conclude that bias potentials on the order of 0.5 eV are required to dissociate CT state, in line with the results reported for one of the best performing NFA, Y6 [38].…”
Section: Dissociation Of the Charge Transfer Statesupporting
confidence: 84%
“…It has been suggested that the 2D assembly of 6TIC has a distinctive advantage of acquiring large intramolecular polarization volume (optical frequency dielectric functions). [ 31 ] Moreover, the intermolecular polarization volume can be directly correlated to the degree and structure of the molecular packing, [ 32 ] which can be greatly enhanced for the NFAs in highly ordered states exhibiting large orbital overlap among molecules in excited states. Thus, these molecular and crystalline characteristics can be reasonably correlated to the spontaneous charge generation observed in this research.…”
Section: Resultsmentioning
confidence: 99%